Writing Skills of Procedural Texts of Grade VII Students of Madani State Middle School, Pekanbaru: Descriptive Statistical Analysis - Putri Fransiska; Elmustian; Tria Putri Mustika (Raja Zulkarnain Education Foundation, 2026)
Procedural texts are included in the narrative-factual text group, which has a core structure of orientation, materials and tools, processes, and conclusions. The dominant linguistic aspect in procedural texts is the paragraph unit per text structure. This study aims to describe the procedural text writing ability of seventh-grade students at SMP Negeri Madani Pekanbaru. The study employed a quantitative approach using a descriptive method. The research was conducted from August 2025 to March 2026, involving 50 students as the population, and all of them were selected as the sample through total sampling technique. The research instrument was a performance test in writing procedural texts. The test construction procedure consisted of determining basic competencies, formulating test indicators, designing the test blueprint, constructing test items, and preparing scoring rubrics. The assessment indicators included text structure, language features, and writing mechanics. Data were collected through students’ writing products and analyzed using descriptive and inferential statistics with IBM SPSS Statistics version 20. The results showed that the students’ procedural text writing ability obtained an average score of 75.28, categorized as sufficient. The text structure aspect obtained an average score of 75.97 (good), language features 78.00 (good), and writing mechanics 61.50 (poor). Thus, students’ procedural text writing ability was categorized as sufficient, with the highest achievement in language features and the lowest in writing mechanics.